Pemanfaatan Youtube sebagai Media Alternatif Pujian Rohani untuk Meningkatkan Komitmen Beribadah Jemaat GKSI Pondok Natai - Yanti, Yanti (Sekolah Tinggi Teologi Injili Arastamar (SETIA) Jakarta, 2025)
Community service at GKSI Pondok Natai aims to overcome low congregational participation in worship through an innovative approach based on digital technology. The main problem is the declining interest of the congregation in worship due to monotonous praise music and the challenges of work in the plantation sector that make it difficult to attend on Sundays. The research method used a qualitative approach through participatory observation and literature study, with stages including pastoral visits, YouTube utilization education, congregation group formation, and member involvement in the service. Program implementation was carried out for four months with a focus on transforming spiritual experiences using digital technology. Results showed a significant increase in congregational attendance of up to 90%, a change in spiritual mindset, and increased enthusiasm for service. In conclusion, the innovative YouTube-based approach successfully transformed congregational participation from passive to active, proving the effectiveness of digital strategies in fostering contemporary spiritual life.